Children ’s literature between the rhythmic structure and the semantic structure A poem of farewell to "poet Nasser Lohishi" model- - Boufas, Abdelhamid (Milev Journal of Research and Studies, 2022)
The present study deals with some rhythmic aspects and their significance for children literature. This has been approached within a framework entitled: “Children literature between the rhythmic and semantic structure: case study of farewell song for the poet "Nacer Louhichi". The study has touched upon the different rhythmic structures such as phonemic, metric and rhetoric, and their relationship with semantics. Within this perspective, these structures were deemed as subsystems included within the text which is considered as a holistic system. Afterwards, the research attempted to find a thread that links the various rhythmic structures with the general meaning of the text, and reveal the functionality of these structures to fit children’s intellectual and bodily capabilities as well as their psychological and social predispositions.